Neurological outcomes and predictive factors in traumatic spinal cord injury patients in the intensive care unit - Danqin Yuan; Yaling Jin; Lihui Chen; Min Tang; Jiuzhou Lin; Weiting Chen (PLoS ONE, 2025)
Background This study aims to analyze the demographic characteristics, clinical features, and neurological outcomes of patients with traumatic spinal cord injury (TSCI) admitted to the Intensive Care Unit (ICU), in order to provide scientific evidence for the prevention and management of TSCI. Methods A retrospective analysis was conducted on data from TSCI patients admitted to the ICU between January 2018 and December 2022. Demographic information, neurological injury characteristics, complications during hospitalization, treatment interventions, and prognosis were comprehensively collected. Based on changes in neurological function before and after treatment, patients undergoing surgery were classified into improvement and non-improvement groups. Neurological recovery was assessed using the American Spinal Injury Association (ASIA) impairment scale. Univariate and multivariate logistic regression analyses were performed to identify key factors influencing neurological recovery. Results A total of 341 TSCI patients were included, with a mean age of 55.2 ± 13.4 years and a male-to-female ratio of 6.3:1. The leading cause of TSCI were high falls (47.5%), traffic accidents (35.8%) and low falls (9.1%). Cervical spinal cord was most common, followed by thoracic and lumbar cord. Among surgical patients, the neurological improvement rate was 14.8%, compared to 12.5% in non-surgical patients, highlighting the potential benefits of surgical intervention. Multivariate analysis revealed that early targeted blood pressure management (MAP ≥ 85 mmHg) (OR=2.296, 95% CI: 1.036–5.086, P = 0.040) and early surgery (≤ 24h) (OR=2.841, 95% CI: 1.088–7.419, P = 0.033) were significant protective factors for neurological improvement. Conclusions Patients with TSCI admitted to the ICU are predominantly middle-aged men, with high falls and traffic accidents being the primary causes. Early blood pressure optimization and timely surgical intervention are significantly associated with improved neurological outcomes.